Experimental studies of thermoelectric parameters of materials forming part of thermoelectric modules - Havryliuk, M. V.; Lysko, V.V.; Rusnak, O. S. (Journal of Thermoelectricity, 2022)
The design of equipment for measuring the parameters of thermoelectric generator and cooling modules is presented, as well as a description of the method for determining the thermoelectric properties of materials used in these modules. The equipment was created on the basis of the absolute method, which makes it possible to determine the parameters of modules in real conditions of their operation and allows instrumental minimization of the main sources of measurement errors. The results of experimental studies of the parameters of thermoelectric modules carried out using the developed equipment are presented. Bibl. 8, Fig. 7, Table. 2.